2015
DOI: 10.1111/ejss.12305
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional pore structure and carbon distribution of macroaggregates in biochar‐amended soil

Abstract: Summary Incorporation of biochar improves the physical properties of soil that are needed for plant growth; in particular, it stabilizes soil's aggregate structure. There has been little research, however, on the effects of biochar on three‐dimensional (3‐D) soil structure and carbon distribution within aggregates. To investigate the effects we amended two soil types (Ultisol and Vertisol) with three types of biochar (at the rate of 40 g biochar kg−1 soil). We separated the macroaggregates (5–7 cm in diameter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…In other words, biochar application increased the water content by 8% and 2% for BC I and BC III respectively indicating that the most important value was observed for BC I. As found in the present study, the improvement of water retention capacities after biochar addition have previously been observed (Cao et al, 2014;Obia et al, 2016) and reported to be due to its porous nature (Yu et al, 2016 BC III had also a positive effect on water use efficiency (Fig. 4c).…”
Section: Barley Germination Testsupporting
confidence: 82%
“…In other words, biochar application increased the water content by 8% and 2% for BC I and BC III respectively indicating that the most important value was observed for BC I. As found in the present study, the improvement of water retention capacities after biochar addition have previously been observed (Cao et al, 2014;Obia et al, 2016) and reported to be due to its porous nature (Yu et al, 2016 BC III had also a positive effect on water use efficiency (Fig. 4c).…”
Section: Barley Germination Testsupporting
confidence: 82%
“…This finding is in contrast to a more passive role that is more typically attributed to biochar where it contributes to soil C sequestration simply due to its recalcitrance. Much of the previous research on biochar has focused on increased soil C storage brought about directly from addition of biochar itself: many types of biochar are relatively stable (particularly those produced at high temperatures) and persistent in soil for extended periods of time (Mašek et al, 2013; Yu et al, 2016; Zimmerman, 2010). In contrast, our results suggest that biochar can play a more active role, by facilitating the physical protection of C (both biochar- and native-derived SOM) in aggregates, at least in the finer textured Yolo soil.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of biochar can be feedstock-specific. Using X-ray micro-computed tomography, Yu et al (2016) characterized the soil pore structure and reported that woodchip and wastewater sludge biochar increased the porosity of soil macroaggregates more than straw biochar.…”
Section: Soil Pore Size Distributionmentioning
confidence: 99%